Crop science in rice : - Matsushima, Seizo (Fuji Publishing Co., Ltd, 1966)
This book deals mainly with when and how the grain yield of rice is determined and can be predicted and increased. Prediction and increase of yeild depend on a study of yeild-determining components and therefore in this chapter an outline is given of these components and their relative importance in enabling yeild to be predicted and increased.